Stem Cell Markers in Neuroblastoma—An Emerging Role for LGR5 - Forgham, Helen; Johnson, Darren; Carter, Noel; Veuger, Stephany; Carr-Wilkinson, Jane (Frontiers in Cell and Developmental Biology, 2015)
The prognostic value of cancer stem cell markers in various cancer subtypes is a well documented research area. Our findings show that the stem cell marker Lgr5 is associated with an aggressive phenotype in neuroblastoma. Here, we discuss these findings within the context of recent studies in several cancers such as lung, colorectal and intestinal cancer, glioblastoma and ewing’s sarcoma. Neuroblastoma continues to be an elusive disease, due to its heterogeneous presentation ranging from spontaneous regression to aggressive metastatic disease and intertwined genetic variability. Currently, the most significant prognostic marker of high risk disease and poor prognosis is amplification of the MYCN oncogene, which is found in approximately 25% of cases [1]. With this in mind, there is still much to learn about the driving mechanisms of this aggressive paediatric tumour. Neuroblastoma development is thought to be the result of aberrant differentiation of the cell of origin, embryonic neural crest cells which then migrate and invade during the developmental stage[2]. Aberrant cells are those which would, under normal conditions form the mature tissues of the sympathetic ganglia and adrenal medulla. Tumours are known to develop indiscriminately along the radius of the sympathetic ganglia, although it is well established that the adrenal glands are fundamentally the most common primary site [3]